2016
DOI: 10.1016/j.ygyno.2016.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Role of cervical cytology in surveillance after radical trachelectomy for cervical cancer

Abstract: Objective There are currently no standard guidelines on the use of Papanicolaou (Pap) tests for surveillance after radical trachelectomy for cervical cancer. The goal of this study was to determine the usefulness of Pap tests in routine surveillance after radical trachelectomy for cervical cancer. Methods Cervical cancer patients who underwent radical trachelectomy from January 2004 through October 2015 and subsequently had at least one Pap test were retrospectively identified. Demographic and clinical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Gynecological examination, if possible under sedation, is important to assess disease characteristics, invasion of adjacent structures, and extension to the pelvic wall. Palpation of the inguinal and supraclavicular lymph nodes is mandatory …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gynecological examination, if possible under sedation, is important to assess disease characteristics, invasion of adjacent structures, and extension to the pelvic wall. Palpation of the inguinal and supraclavicular lymph nodes is mandatory …”
Section: Resultsmentioning
confidence: 99%
“…Patients who will undergo PE surgery should have their cases, whenever possible, previously discussed by a multidisciplinary team, which should be composed of the clinical/surgical medical staff, a physiotherapist, a nurse, a psychologist, a stomatotherapist, and a nutritionist …”
Section: Resultsmentioning
confidence: 99%
“…These anomalies lead to extensive investigations and generate high levels of anxiety. In the series of Brown et al, 21 up to 59% of the patients had at least 1 abnormal Pap test during follow-up after radical trachelectomy, yet none developed a cancer recurrence. They concluded that the routine use of cervical cytology as surveillance after radical trachelectomy does not appear to substantially impact management decisions.…”
Section: Follow-upmentioning
confidence: 91%
“…They concluded that the routine use of cervical cytology as surveillance after radical trachelectomy does not appear to substantially impact management decisions. 21 Moreover, Slama et al 22 analyzed their recurrence pattern after trachelectomy and noted that most of the recurrences were central or pelvic. Only 2 patients were symptomatic.…”
Section: Follow-upmentioning
confidence: 99%
“…Regardless of the results obtained, no recurrence was found in 41 patients involved in the study. 71 Many centers implement MRI examinations at 6, 12, and 18 months. However, the interpretations are often difficult due to anatomical changes.…”
Section: Follow-upmentioning
confidence: 99%